Exploring the phenotypic diversity of Eragrostis tef for biomass and grain production under optimum growth conditions - Mengistu, Mitiku Asfaw; Yim, Won Cheol; Solomon, Juan K. Q.; Cushman, John C. (Frontiers in Plant Science, 2025)
IntroductionTef or Teff [Eragrostis tef (Zucc.) Trotter)] is a C4 photosynthesis tropical grass species within the Poaceae valued for its high-quality forage, fodder, and highly nutritious, gluten-free grain while showing great potential as a bioenergy crop due to its high biomass productivity and climate resilience. Here, we document the extensive phenotypic diversity of 368 E. tef accessions within the United States Department of Agriculture (USDA)-Agricultural Research Service (ARS) national germplasm collection.MethodsTwo morphological (e.g., panicle morphology and seed color) and 11 quantitative agronomic (e.g., including fresh weight, dry weight, straw yield, seed yield, harvest index, plant height, panicle length, tiller count, floret count, hundred-seed weight, and seed area) traits were characterized under idealized growth conditions.ResultsFive major panicle forms were identified including very loose, loose, semi-loose, compact, and, very compact, which were present in 24%, 25%, 25%, 18%, and 8% of accessions, respectively. Accessions with very compact panicles showed the highest biomass production and plant height, whereas accessions with loose and very loose panicle forms showed the highest tiller counts, seed yield, and harvest indices. White-seeded accessions were more numerous (55%) than brown-seeded accessions (45%) with white seeds being more common in very compact, compact, and semi-loose panicle forms and brown seeds being more common in loose and very loose panicle forms. Correlation analysis revealed positive associations among fresh weight, dry weight, straw yield, and plant height was well as seed yield and harvest index. Hundred-seed weight was positively correlated with seed area, plant height, and panicle length. Principal component analysis identified fresh weight, dry weight, and straw yield as major contributors (72.6%) to total trait variation. Hierarchical agglomerative clustering analysis revealed five distinct groups based upon the quantitative agronomic traits.DiscussionThese data provide an invaluable resource for genome-wide association studies, stratified sampling, and parental line selection for ongoing E. tef breeding programs.